KEBERHASILAN TERAPI MENGGUNAKAN METOTREKSAT PADA KASUS PSORIASIS VULGARIS ANAK DERAJAT BERAT: SEBUAH LAPORAN KASUS - Theodorus, Prilly Pricilya; Manuputty, Amanda Gracia; Bandjar, Fitri Kadarsih; Tanamal, Rita Sugiono; Tanasal, Hanny (Pattimura University, 2024)
Introduction: Psoriasis is a chronic-relapse erythrosquamous dermatoses disease. Psoriasis occurs in any age with one-third of the cases start during childhood. Strategy in managing psoriasis is based on the severity and consideration towards patient’s medical condition. Case: A 12-year-old male child was admitted to dermatovenereologist clinic with reddish patch covered in thick scales that occur on almost his entire body. The condition, started when he was 3 years old, was oftentimes relapsing and worsened within the last 2 months. Patient frequently went to doctor and prescribed with ointment. The condition keeps relapsing, though there was improvement after treatment. Physical examination showed sharply marginated erythrosquamous macules are over 30% of body surface area, Kaarvetsvlek phenomenon, Auzspit sign, and PASI score 30.8. Histopathological examination present elongation of rete ridges and microabscess Munro. Patient were given 1 cycle of Methotrexate (MTX) and showed significant improvement in PASI score. Discussion: Types of psoriasis treatment are topical, systemic, phototherapy and biologic agent. MTX still remain one of the systemic treatment especially for moderate to severe psoriasis in children. Oral MTX is recommended because it is more convenient than parenteral administration. Conclusion: Pediatric psoriasis occurs in one-third of the cases and may affect patient’s physical and psychological health. MTX acts as antiproliferation and antiinflammation treatment for moderate-severe psoriasis and recalcitrance lesion to topical steroid. Education about the disease is important for treatment success and risk of relapse reduction.